Changes in the concentration of polyamines in human milk during lactation - Doosti, Behzad (My University, 2019)
It is generally agreed that human breast milk is the most prefect food source for the newborns. It contains all macronutrients as well as bioactive components that are crucial for the baby’s development. Polyamines, putrescine spermidine and spermine are amongst the bioactive compounds in breast milk. Polyamines are provided by biosynthesis and exogenous uptake. Polyamines are the essential compounds for the cellular growth and proliferation, they are involved in some important cellular functions such as DNA and RNA synthesis, modulating gene expression and cell membrane stabilizing. Human milk contains high concentrations of polyamines especially spermidine and spermine and lower amount of putrescine. Early intake of polyamines during infancy is important for, intestinal maturation, reduction of mucosal permeability and prevention of food allergies. Content of polyamines in breast milk is affected by several factors such as the stage of lactation, genetic influences and dietary pattern. The aim of this study was to investigate the changes in the concentration of polyamines in breast milk samples at different stages of lactation. 84 human milk samples were obtained from 13 Chinese mothers at different times of lactation. Two mothers gave birth by caesarean. To investigate the possible influence of this factor statistical analysis was performed twice, once with participation of these two mothers and once with exclusion of them. Dansylated derivatives of polyamines were analysed by high performance liquid chromatography (HPLC). Spermidine was the predominant polyamine, followed by spermine and putrescine. Level of putrescine remained low during lactation. Spermidine level was significantly higher at the two weeks timepoint compared to later time points. Spermine level did not differ between time points but the tendency to decrease toward the lactation stages was clear. Due to the small sample size no association between the mode of delivery and the level polyamines in breast milk samples was found. High level of spermidine and spermine during the first two weeks of lactation can be related to their functions on early immune and intestinal maturation. Since polyamine content of human milk can be influenced by environmental factors, further studies on changes in milk polyamines related to them are encouraged.
Keywords: human milk, polyamines, putrescine, spermidine, spermine, dietary polyamines, HPLC.